2020
DOI: 10.1111/ajco.13359
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and toxic effects of prophylactic cranial irradiation in stage II–III non–small cell lung cancer: A meta‐analysis

Abstract: Objective: To determine the role of prophylactic cranial irradiation (PCI) in non-small cell lung cancer (NSCLC) patients using meta-analysis. Methods: PubMed, Embase, the Cochrane Database of Systematic Review and the China National Knowledge Infrastructure databases were systematically searched for studies published between 1 January 1980 and 31 March 2019. Search terms included "non-small cell lung cancer," "prophylactic cranial irradiation" and "clinical trials." The research data extracted from above stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…39 Although a meta-analysis is available on the adverse events of PCI in stage II or III non-SCLC that shows a higher rate of fatigue in PCI patients and a comparable cognitive disturbance between groups, no review is available on SCLC patients. 40 In the current review, 9 studies assessed the adverse events of PCI in SCLC patients, but because of the heterogeneity in reporting outcomes, quantitative analyses were not possible. Accordingly, the North Central Cancer Treatment Group study on the use of PCI in SCLC patients showed significantly higher rates of lethargy and alopecia.…”
Section: Discussionmentioning
confidence: 99%
“…39 Although a meta-analysis is available on the adverse events of PCI in stage II or III non-SCLC that shows a higher rate of fatigue in PCI patients and a comparable cognitive disturbance between groups, no review is available on SCLC patients. 40 In the current review, 9 studies assessed the adverse events of PCI in SCLC patients, but because of the heterogeneity in reporting outcomes, quantitative analyses were not possible. Accordingly, the North Central Cancer Treatment Group study on the use of PCI in SCLC patients showed significantly higher rates of lethargy and alopecia.…”
Section: Discussionmentioning
confidence: 99%